Relationship between Mathematical Communication Ability and Adversity Quotient of Junior High School Students - Yosy Candraningsih; Elah Nurlaelah; Jarnawi Afgani Dahlan (PYTHAGORAS Jurnal Matematika dan Pendidikan Matematika, 2025)
Students' perceptions of the difficulty of mathematics often influence their mathematical abilities. Students who possess a strong Adversity Quotient (AQ) are likelier to demonstrate improved mathematical abilities, particularly in mathematical communication abilities. This study examines the relationship between mathematical communication ability and students' Adversity Quotient (AQ). The research employed a correlational method, with a sample of 31 ninth-grade students from a junior high school in Bandung City during the 2024/2025 academic year. Data were collected through mathematical communication ability tests and an Adversity Quotient (AQ) questionnaire. The collected data were analyzed in two stages: an Exploratory Data Analysis (EDA), which included normality and linearity tests, followed by Confirmatory Data Analysis (CDA), which used the Pearson correlation test. The results revealed a correlation coefficient of 0.672, indicating a medium-level relationship between students' mathematical communication ability and their Adversity Quotient (AQ).